Cluster analysis of precipitation contamination - LI Zhen-yu; WANG Feng-ping; ZHU Yin-mei (浙江大学学报. 农业与生命科学版)
Analysis was performed to identify the event-to-event variations in precipitation. Individual rain events were applied for analysis and selected as variables. Nine major ions measured in rain event were subjected as observations of cluster analysis. After performing cluster analysis, six clusters were retained as the optimal describing form. According to the concentration of ions in each cluster, above six clusters were classified as follows: hydrogen ion cluster (cluster 1), ion cluster without characteristic (cluster 2), chloridion and sodium cluster (cluster 3), sulfate and ammonium cluster (cluster 4), calcium and magnesium cluster (cluster 5) and nitrate cluster (cluster 6). Obviously, cluster 1 pertained to acid precipitation and cluster 3 was associated with marine precipitation while cluster 1 and 5 were of the transition types. Moreover, cluster 4 and 6 were clusters with high ion concentration. However, strong acid precipitation and high ion concentration precipitation couldn't come under the same type. Precipitation acidity was highly correlated with alkalescent components in rainwater. Rainfall was strongly acidic only when the concentration of ammonium and calcium ions, especially the former, was relatively low. The precipitation (cluster 1, cluster 2 and cluster 3) controlled by north flows including northeast monsoon flow and frontal system flow was strongly acidic and was caused by pollutants during long distance transportation. cluster 4, cluster 5 and cluster 6 that had a relatively high ion concentration were mainly polluted by source of close quarters.